2014
DOI: 10.1182/blood-2013-03-492447
|View full text |Cite
|
Sign up to set email alerts
|

A novel and essential role for FcγRIIa in cancer cell–induced platelet activation

Abstract: Key Points• The immune receptor FcgRIIa is a key mediator of tumor cell activation of platelets in the circulation.• Secretion of adenosine 59-diphosphate from dense granules is the primary response of platelets to activation by tumor cells.Platelets play a role in cancer by acting as a dynamic reservoir of effectors that facilitate tumor vascularization, growth, and metastasis. However, little information is available about the mechanism of tumor cell-induced platelet secretion (TCIPS) or the molecular machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 50 publications
3
58
0
3
Order By: Relevance
“…For instance, Munc13-4 deficient mice, whose platelets lack the ability to secrete dense granule components such as ADP and ATP, or mice deficient in the P2Y 2 -ATP receptor on endothelial cells, have been shown to exhibit a significant decrease in melanoma (B16) and breast carcinoma (LCC) cell extravasation and metastasis colony formation as compared to wild-type mice (60). Moreover, platelet-derived ADP has been shown to promote tumor cell-induced platelet aggregation (61), a potential strategy utilized by several tumor cell lines to evade the immune system and resist arterial shear stress during the hematogenous journey (36). Thus, platelet-bound adhesive molecules, platelet-derived soluble molecules and fibrin can synergistically enhance the ability of CTCs to traverse the endothelial cell barrier, penetrate the parenchyma and establish a metastatic lesion.…”
Section: The Cross-talk Between the Hemostatic And The Malignant Smentioning
confidence: 99%
“…For instance, Munc13-4 deficient mice, whose platelets lack the ability to secrete dense granule components such as ADP and ATP, or mice deficient in the P2Y 2 -ATP receptor on endothelial cells, have been shown to exhibit a significant decrease in melanoma (B16) and breast carcinoma (LCC) cell extravasation and metastasis colony formation as compared to wild-type mice (60). Moreover, platelet-derived ADP has been shown to promote tumor cell-induced platelet aggregation (61), a potential strategy utilized by several tumor cell lines to evade the immune system and resist arterial shear stress during the hematogenous journey (36). Thus, platelet-bound adhesive molecules, platelet-derived soluble molecules and fibrin can synergistically enhance the ability of CTCs to traverse the endothelial cell barrier, penetrate the parenchyma and establish a metastatic lesion.…”
Section: The Cross-talk Between the Hemostatic And The Malignant Smentioning
confidence: 99%
“…FcgRIIa signals through a single ITAM in its cytosolic domain and is a critical mediator of platelet activation in immune thrombocytopenia, [3][4][5] heparin-induced thrombocytopenia, 6 bacterial infection, 7,8 and cancer. 9 CLEC-2, a type II transmembrane protein, signals via a single YxxL sequence known as a hemITAM and is the receptor for the type I transmembrane GP podoplanin, which is widely expressed outside of the vasculature, including lymphatic endothelial cells, type 1 lung alveolar cells, lymph node stromal cells, and the choroid plexus epithelium. Podoplanin is also present on inflammatory macrophages 10,11 on a subset of activated T-helper (Th)17 cells.…”
Section: Introductionmentioning
confidence: 99%
“…45 Interestingly, recent evidence suggests that these anticoagulants can also selectively inhibit platelet release of proangiogenic proteins and diminish platelet-mediated angiogenic response. 21 Finally, blockade of platelet Fcg receptor IIa and a IIb b 3 receptors would also be logical approaches, 7 in addition to blockade of the P2Y 2 receptor on endothelial cells or its downstream signaling pathway. 20 However, these too will require rigorous preclinical testing, especially as prasugrel, a potent P2Y 12 receptor blocker used in the treatment of cardiovascular disease, was found to be associated with a higher rate of colonic malignancy in a large study.…”
Section: Targeting Paraneoplastic Thrombocytosis In Anticancer Therapymentioning
confidence: 99%
“…6 More recently, Mitrugno et al demonstrated that tumor cells could directly induce platelet activation and secretion of dense granules containing adenine nucleotides via the platelet Fcg receptor IIa. 7 Platelet activation by tumors throughout all phases of the metastatic cascade leads to the release of platelet-derived factors stored in their granules that then mediates the inflammatory, proliferative, and proangiogenic activities of platelets to promote tumor growth, tissue invasion, and metastasis. 8,9 Conversely, platelets activated by tumor cells play major roles in aiding and abetting tumor progression.…”
Section: The Hijacking Of Platelet Functions By Malignant Tumorsmentioning
confidence: 99%